Functional Characterisation and Analysis of the Soluble NKG2D Ligand Repertoire Detected in Umbilical Cord Blood Plasma - Cox, Steven T.; Danby, Robert; Hernandez, Diana; Laza-Briviesca, Raquel; Pearson, Hayley; Madrigal, J. Alejandro; Saudemont, Aurore (Frontiers in Immunology, 2018)
We previously reported that cord blood plasma (CBP) contains significantly more soluble NKG2D ligands (sNKG2DLs), such as sMICB and sULBP1, than healthy adult plasma. Viral infection or malignant transformation upregulates expression of NKG2DL on affected cells, leading to NKG2D-mediated NK cell lysis. Conversely, sNKG2DL engagement of NKG2D decreases NK cell cytotoxicity leading to viral or tumour immune escape. We hypothesised that sNKG2DLs detected in CBP may represent an additional fetal-maternal tolerance mechanism. To further understand the role of sNKG2DL in pregnancy and individual contributions of the various ligand types, we carried out functional analysis using 181 CBP samples. To test the ability of CBP to suppress the function of NK cells in vitro, we measured expression of NKG2D, CD107a and IFN-γ in NK cells from control donors after exposure to 181 individual CBP samples and characterised the sMICA, sMICB and sULBP1 content of each one. Furthermore, to detect possible allelic differences between samples that may also affect function, we carried out umbilical cord blood typing for MICA and MICB coding and promoter allelic types. Strongest functional correlations related to increasing concentration of exosomal sULBP1, which was present in all CBP samples tested. Additionally, common MICB alleles, such as MICB*005:02, resulted in increased concentration of sMICB. Interestingly, MICB*005:02 uniquely associated with 8 different promoter types. Among promoter polymorphisms, P2 resulted in the highest expression of sMICB and P9 the least and was confirmed using luciferase reporter assays. Higher levels of sMICB associated with lower IFN-γ production, indicating that sMICB also suppressed NK cell function. We also examined the MICA functional dimorphism encoding Met or Val at residue 129 associated with strong or weak NKG2D binding, respectively. Most sMICA expression associated with Val/Val, some with Met/Val but none with Met/Met and, counter-intuitively, the presence of sMICA in CBP increased NK cell cytotoxicity. We propose a model for fetal-maternal tolerance whereby NK cell activity is limited by sULBP1 and sMICB in CBP. The release of 129val sMICA with weak NKG2D signalling may reduce the overall net suppressive signal and break tolerance thus allowing fetal NK cells to overcome immunological threats in utero.